WAWASAN YANG MENINGKATKAN: PERKEMBANGAN E-BOOKLET PROGRESIF DALAM SUHU DAN PANAS - Afrida, Juniar; Ramadhan, Muhammad Daffa Syahrul; Alaidin, Samsul Fala (EduFisika: Jurnal Pendidikan Fisika, 2023)
This study aims to evaluate the feasibility of an E-Booklet centered on temperature and heat materials. Employing the Research and Development (R&D) methodology, the research adheres to the Alessi and Trollip model, progressing through planning, design, and development stages. Validation instruments, encompassing validation sheets for both material and media, were employed. The validation process involved six material experts, including lecturers and teachers, along with three media experts. Results demonstrate the high feasibility of the developed E-Booklet for temperature and heat materials, attaining an average score of 95.58%, categorized as "very feasible." Material expert validation from lecturers yielded an average score of 97.87%, categorized as "very decent," while validation from teachers resulted in an average score of 94.12%, also categorized as "very decent." Media expert validation produced an average score of 94.75%, falling within the "very decent" category. In conclusion, the developed E-Booklet for temperature and heat materials proves highly suitable for integration into the learning process. Implications of the study highlight the importance of integrating innovative digital resources to enhance educational experiences. This research contributes to advancing educational practices through the creation of effective and engaging digital learning materials in the field of temperature and heat.